Anti-Vascular Endothelial Growth Factor Injection in Wet Age-Related Macular Degeneration - M. Usman Salim; AK Ansyori; Ramzi Amin (Sriwijaya Journal of Ophthalmology, 2019)
Introduction. AMD is a macular progressive degeneration that arises at the age of more than 50 years, which is characterized by the presence of drusen which is a deposit of material between the retinal pigment epithelium (RPE) and the Bruch membrane. The prevalence of AMD is 29.2% unilateral and 70.8% bilateral. In unilateral wet AMD, 50% will develop on the other eye in a period of 5 years. Case Presentation. A woman, Mrs. S, 59 years old, civil servant working, located in the city, came to the Polyclinic RSMH on January 21, 2019. Anamnesis (Auto-anamnesis) the main complaint of vision of the left eye blurred since, 2 months ago. Since about two months ago, sufferers complained of vision in the left eye blurred, blurred felt suddenly, darker vision in the middle. Since about two weeks ago, sufferers complained that his left eye vision had become blurred. The view in the middle is covered with black shadows and accompanied by waves. Working diagnosis of macular oculi sinistra ec wet age-related macular degeneration. The treatment is informed consent, Pro injection of anti-VEGF intravitreal oculi sinistra, Pro laboratory check, Pro X-ray of thorax PA, Pro consul of internal medicine. Conclusion. A clinically significant case of macular edema (CSME) has been reported that is treated with intravitreal anti-VEGF combined with focal photon photocoagulation laser. A woman aged 55 years, with complaints of vision both eyes blurred since ± 6 months ago.